TEMA DAN FAKTA-FAKTA CERITA DALAM NOVEL DARI TANAH HARAM KE RANAH MINANG KARYA UMMUKI - Astrid Widia Murni; Wachid Purwanto Eko Purwanto (PIKTORIAL : Journal of Humanities, 2019)
Novels are long essays of prose containing a series of stories of a person's life with those around him highlighting the character and nature of each actor. This research was conducted with a qualitative descriptive method. The object of this research is novel sentences which include themes and facts of the story. The data in this study are excerpts from Ummuki's Dari Tanah Haram ke Ranah Minang. The theme contained in the novel is